Assessing perceived business success as a reflective-formative (Type II) second-order construct using PLS-SEM approach - Tehseen, Shehnaz *; Qureshi, Zuhaib Hassan; Fatema Johara,; Ramayah, T (Universiti Malaysia Terengganu, 2019)
This paper describes the process of validating “business success”as a reflective-formative construct using the Partial Least Squares-Structural Equation Modeling (PLSSEM) approach. This second-order latent variable has been operationalized with four dimensions, namely perceived financial performance, perceived non-financial performance, perceived business growth and perceived performance relative to competitors. These dimensions do not share a common theme and are distinctly different. Moreover, business success is a phenomenon that occurs with the presence of these constructs. In other words, it is formed by these constructs, thus, it should be measured as a Type II reflective-formative second-order construct. This paper has established the reflective-formative relationship among first-order and second-order constructs. We recommend considering and measuring business success as a reflective-formative second-order latent variable because the misspecification at second-order construct could cause drastic changes in R 2 values and in the values of path coefficients.